On the Experimental Investigation of Bone Fracture Recovery Process Using an Ultra-Wideband Planar Monopole Antenna - Shaik Rizwan; Kanaparthi V. Phani Kumar; Sandeep Kumar Palaniswamy (International Journal of Antennas and Propagation)
In this paper, a noninvasive bone fracture monitoring system is developed using a planar monopole antenna. The proposed antenna provides an ultra-wideband response, and its overall size is 18 × 19 × 0.8 mm3. The proposed ultra-wideband monopole (UWM) antenna has a maximum measured gain of 3.77 dBi, and the maximum SAR value for an input power of 18 dBm is less than 1.6 (W/kg) (1 g). A bovine tibia is experimentally tested using a proposed UWM antenna to monitor the fracture recovery process and then further analysed using principle component and linear regression analysis. In addition, a microcontroller with a wireless communication module is developed to monitor the data in an Android application. The proposed system could be a promising approach for developing a portable, noninvasive monitoring device.